CHARACTERISTICS AND FIGURES OF FRESH TILAPIA BACTERIA FROM TAMBAK SAWIYOH SIDOARJO - Sara Wijimulyati; Erfan Andrianto Aritonang; Eka Rista Efrem Burga (Universitas Airlangga, 2020)
ABSTRACTThis study aims to analyze characteristic and calculate the number of bacterial contamination of fresh nila fish from Sawiyoh pond Sidoarjo, East Java. A total of 30 fresh nila fish were taken and examined at the Microbiology Laboratory Faculty of Medicine Wijaya Kusuma Surabaya University. This research is a descriptive study with observational methods. The step of bacterial enrichment was carried out on BPW (Buffered Pepton Water) media. The bacterial identification procedure uses selective media SSA (Salmonella-Shigella Agar), Gram staining, and tests on TSIA media (Triple Sugar Iron Agar). The procedure for calculating the total bacteria using TPC (Total Plate Count) on NA (Nutrient Agar) media. The results on selective SSA media in 30 samples showed suspect Salmonella sp. with the characteristics of colorless colonies with black dots in the middle. The results of Gram staining in 30 samples showed that the bacteria were Gram negative in the form of rods. Test results on TSIA media identified one positive sample of Salmonella sp. (sample 09) with characteristics of the red slope of the media, the base of the media is yellow, and H2S is formed. The results of the calculation of total bacteria by the TPC method showed that the total bacterial total was 15.8 x 105 CFU / gram. The limit of microbial contamination according to the 2009 SNI for fresh fish is 5 x 105 CFU / gram so that fresh nila fish from Sawiyoh Sidoarjo pond has a number of bacterial contamination above the stipulated threshold.Keywords: Nila Fish, Gram Staining, Salmonella sp., Salmonella-Shigella Agar, Total Plate Count, Triple Sugar Iron Agar